The last of the high kings - Thompson, Kate, 1956- (Greenwillow Books, 2008)
When eleven-year-old Jenny Liddy, in turmoil over learning that she is a changeling, makes a deal with a devil creature, she endangers the human race but her own cleverness, her human and fairy fathers, and the last of Ireland's high kings help to make things right.